New Marketing Appeal for “Made in Italy Food” in China Amid Rising Consumption and Transaction Costs - Pin, Antonio De (Business, Management and Economics: Research Progress Vol. 2, 2024)
This chapter analyses the market potentiality of «Made in Italy food» and focuses on some emerging issues concerning Italian specialties characterized by higher competitiveness. Starting from the definition of «Made in Italy food», the paper addresses the topic of food safety, analysing policies, and legislation. Following an approach from macro to micro aspects, market trends are highlighted, and a ranking analysis is carried out, emphasizing the positioning of Made in Italy. Concerns related to transaction costs, information asymmetry, and adverse selection are discussed and the Italian-sounding phenomenon is spotted. Growing practices of unfair competition, such as food piracy, result in several forms of market failure, damaging the segmentation strategies of Italian companies. Findings propose an estimate of unfair business and offer special indexes of evaluation. Finally, policy and business implications are addressed and attractive, and multiple fields for future research are suggested. Chinese food habits are currently experiencing rapid changes. The increasing consumer purchasing power results in the adoption of a new lifestyle and diet - both in quantity and quality. The consumption trend causes a sudden boom in food imports, with China becoming the world’s largest market and an essential opportunity for Italian business. Among Italian specialties characterized by higher competitiveness, it results in wine is the first in the ranking of Italian foodstuffs in China, followed by chocolate, pasta, and bakery, as olive oil and many other typical foods such as meat, sausages, hams, and dairy products highlight excellent performances. Although the Chinese market enjoys higher appeal, it is also suffering from growing concerns about transaction costs, information asymmetry, and adverse selection, for which it becomes essential to identify measuring tools. The success of Made in Italy foments indeed Italian-sounding phenomena. Growing practices of unfair competition like food piracy can result in many kinds of market failure, due to the lack of adequate regulation. The segmentation strategies of Italian companies can be heavily damaged by such imitation activities, with huge losses of income for true «Made in Italy food».